Design and Simulation Analysis of an Impact-resistant Flexible Joint - Li Yang; Cui Shipeng; Liu Yiwei (Jixie chuandong)
An impact-resistant flexible joint with passive compliant mechanical structure and active compliant control is designed to cope with the dynamically-changing work environments and human-robot interaction issues. A series elastic actuator which uses a novel torsional elasticity instead of traditional torsional spring as elastic element to make the joint more integrated is embedded between the joint motor and load. The dynamics model of the flexible joint is established. Then,the impedance control strategy for the joint are made based on the sensory ability of multiple sensors. At last,the effectiveness of the control strategy is verified by the combined simulations on the joint virtual prototype with ADAMS and Simulink,which shows that the flexible joint has good property of torque compliant and impact-resistant,making it possible to adapt to variable environments.